Peningkatan Akses Layanan Kesehatan Digital Melalui Sosialisasi Dan Pemanfaatan Mobile Jkn Bagi Masyarakat Pesisir Bintalahe, Kecamatan Kabila Bone Kabupaten Bone Bolango - Daud, Ayudhita Cahyani; Mursyidah, Andi; Muthmainnah, Muthmainnah; Massa, Mesalina Sukardi (Damhil: Jurnal Pengabdian kepada Masyarakat, 2025)
The limited level of digital health literacy among coastal communities in Bintalahe Village has resulted in the suboptimal utilization of the Mobile JKN application. Although most community members own smartphones, many are still unaware of the functions and benefits of Mobile JKN or experience technical difficulties in its use. This condition causes the community to remain dependent on inefficient manual administrative services. The objective of this activity was to enhance access to and utilization of digital health services through socialization activities and assistance in using the Mobile JKN application. The implementation method employed a participatory approach through direct educational socialization and hands-on assistance in practicing the use of the Mobile JKN application. The results of the activity indicate an improvement in community understanding and skills in operating Mobile JKN, including checking membership status and independently registering for healthcare service queues. This activity contributes to increasing the efficiency of access to health services and reducing dependence on manual services. The activity also aligns with the achievement of the university’s Key Performance Indicators. Furthermore, continued collaboration between BPJS Kesehatan and primary healthcare centers should be optimized by strengthening digital education, increasing the intensity of socialization, and developing supporting technological infrastructure.